FIZIK BAKALAVRLARNI KASBIY FAOLIYATGA TAYYORLASHDA LOYIHAVIY TA’LIM TEXNOLOGIYALARINI QO‘LLASH METODIKASI - Ismanova, O.T. (SCIENCE and SOCIETY, 2025)
Today, each higher education, based on its characteristics, capabilities and the "social order" of society, the correct development of the content of education is an urgent task the correct organization of the activities of professors-teachers and students. This study is based on the fact that independent activity is significant in project-based learning for the formation of students' research skills. At the same time, methods are shown for the formation of generalized competencies of students.
Keywords: higher education; foreign experience; student; project activity; physics; concept; research; research skills